1977
DOI: 10.1016/0006-8993(77)90729-6
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and vomeronasal deafferentation of male hamsters: Histological and behavioral analyses

Abstract: Deafferentation of the vomeronasal system by cutting the vomeronasal nerves severely impaired mating behavior in 44% of male hamsters over a 1--2 month period of postoperative testing, but the remaining males mated normally after the surgery. Damage to the main olfactory bulbs, concomitant to vomeronasal nerve cuts, did not account for this behavioral difference. Subsequent deafferentation of olfactory system by intranasal infusion of zinc sulfate solution (5 g ZnSO4--7H2O in 95 ml 0.5% NaCl) had no effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(90 citation statements)
references
References 50 publications
5
84
1
Order By: Relevance
“…In the control of male hamster mating behavior, nonvolatile cues detected in the vomeronasal organ are more important than volatile odors transduced in the olfactory mucosa. Selective destruction of the olfactory mucosa by nasal irrigation with zinc sulfate does not interrupt mating, while severing the vomeronasal nerves blocks sexual activity in 0-44% of males (Winans and Powers, 1977). However, combining zinc sulfate with vomeronasal nerve cuts eliminates copulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the control of male hamster mating behavior, nonvolatile cues detected in the vomeronasal organ are more important than volatile odors transduced in the olfactory mucosa. Selective destruction of the olfactory mucosa by nasal irrigation with zinc sulfate does not interrupt mating, while severing the vomeronasal nerves blocks sexual activity in 0-44% of males (Winans and Powers, 1977). However, combining zinc sulfate with vomeronasal nerve cuts eliminates copulation.…”
Section: Discussionmentioning
confidence: 99%
“…EXPERIMENT 1 We have previously shown that ZS treatment abolishes detectability of either amyl acetate or FHVS as tested by a Y-maze discrimination task 2 days after treatment [35]. At this time, over 90% of the olfactory epithelium is destroyed, whereas the VNO epithelium is unaffected [42]. Further, we have found that ZS treatment by itself has no effect on male sexual behavior but renders all animals vulnerable to the effects of VN deafferentation.…”
Section: Attraction To Fhvsmentioning
confidence: 95%
“…This procedure also destroys afferents from the olfactory mucosa to the main olfactory bulb (MOB), connections of the vomeronasal organ (VNO) with the accessory olfactory bulb (AOB), the nerves of the septal olfactory organ and the nervus terminalis [2,5]. Although the contribution which each of these systems might make to the behavioral effects of bulbectomy in any species has not been ascertained, recent work in this laboratory has indicated that the olfactory and vomeronasal systerns together comprise an essential substrate in the regulation of male hamster copulation [36,42]. Although deafferentation of the olfactory system alone by intranasal infusion of zinc sulfate has no effect on mating behavior in male hamsters, combined olfactory and vomeronasal deafferentation eliminates copulation in all animals and thus mimicks the effect of bulbectomy.…”
Section: Hamstermentioning
confidence: 99%
See 2 more Smart Citations